Pengaruh Servicescape, Kualitas Layanan, dan Persepsi Harga Terhadap Kepuasan Konsumen pada Larissa Aesthetic Center Cabang Purwokerto - Ady Achadi; Intan Nur Septiani; Tri Esti Masita (J-MAS (Jurnal Manajemen dan Sains), 2021)
The purpose of this study was to analyze the effect of servicescape, service quality and price perception on consumer satisfaction at Larissa Aesthetic Center Purwokerto. The research population is the consumers of Larissa Aesthetic Center Purwokerto, with a sample of 104 respondents. The sampling technique used was accidental sampling. Research method using multiple linear regression. The results of the study show that servicescape and service quality have a positive and significant effect on consumer satisfaction at Larissa Aesthetic Center Purwokerto. Price perception has not significant effect on consumer satisfaction at Larissa Aesthetic Center Purwokerto. This finding implies the need to maintain and improve the concept of the existing servicescape by adding instructions to the room to make it easier for consumers to understand the function of the room at the Larrissa Aesthetic Center Purwokerto. In addition, providing security guarantees and the risk of damage as well as paying attention to the neatness of the appearance of employees in order to add positive value to the company.